2012
DOI: 10.1371/journal.pone.0038506
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activation and Functional Connectivity during Motor Imagery of Bimanual Everyday Actions

Abstract: Bimanual actions impose intermanual coordination demands not present during unimanual actions. We investigated the functional neuroanatomical correlates of these coordination demands in motor imagery (MI) of everyday actions using functional magnetic resonance imaging (fMRI). For this, 17 participants imagined unimanual actions with the left and right hand as well as bimanual actions while undergoing fMRI. A univariate fMRI analysis showed no reliable cortical activations specific to bimanual MI, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 73 publications
3
29
0
Order By: Relevance
“…A last study by the same group of researchers confirmed these findings, and further showed that motor execution has some increased causal connections because of additional processes for the overt behavior stage (Gao et al, 2011). Taken together, these experimental studies highlight the advantages of studying functional and/or effective connectivity through fMRI to expand our understanding of the neural underpinnings of MI (see also Szameitat et al, 2012).…”
Section: Fmri Advances In the Study Of Motor Imagerymentioning
confidence: 59%
“…A last study by the same group of researchers confirmed these findings, and further showed that motor execution has some increased causal connections because of additional processes for the overt behavior stage (Gao et al, 2011). Taken together, these experimental studies highlight the advantages of studying functional and/or effective connectivity through fMRI to expand our understanding of the neural underpinnings of MI (see also Szameitat et al, 2012).…”
Section: Fmri Advances In the Study Of Motor Imagerymentioning
confidence: 59%
“…The generation of obvious as compared to creative moves in real-life soccer decision-making situations revealed activations in a mainly leftlateralized network including the cuneus, middle temporal gyrus, the rolandic operculum, along with smaller activation clusters involving the left angular and postcentral gyrus, and the left pallidum. Overall, this network of brain regions supports various higher-order cognitive functions such as semantic information processing (Binder et al, 2009), visual and motor imagery (Kosslyn, Ganis, & Thompson, 2001;Szameitat, McNamara, Shen, & Sterr, 2012), likewise the processing and integration of sensorimotor and somatosensory information (Eickhoff et al, 2010). Especially the cluster involving the rolandic operculum appears to overlap with a cortical network that is thought to be implicated in self-referential processes involving self-location in space (Ventre-Dominey, 2014), by integrating visual, vestibular, and somatosensory information to "generate a multi-modal neuronal representation of subject motion and orientation in space" (Karnath, 2001, p.572; see also Eickhoff, Weiss, Amunts, Fink, & Zilles, 2006;Eickhoff et al, 2010;Lopez, Blanke, & Mast, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The premotor cortex is critical for rhythmical bimanual coordination (Christensen et al, 2013;Goerres et al, 1998;Hinder et al, 2012;Sadato et al, 1997;Szameitat et al, 2012), as part of a dorsal pathway that mediates sensorymotor interactions for externally guided movements (Goodale et al, 2003). In particular, age-related increased functional connectivity between the left dorsal and right ventral premotor areas reflects their key role in the present bimanual coordination network with some lateralization specificity (see Jackson and Husain, 1996).…”
Section: Relationship Between Resting State Functional Connectivity Amentioning
confidence: 99%